IMPLEMENTATION OF WORKER REGISTRATION AS PARTICIPANTS OF EMPLOYMENT SOCIAL SECURITY ADMINISTRATORS IN PRIVATE COMPANIES IN PEKANBARU CITY - Sihotang, Tunggul; Afrita, Indra; Harahap, Irawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRACT Background: Article 15 paragraph (1) of Law Number 24 of 2011 concerning BPJS, regulates the obligation of employers to register themselves and their workers as BPJS Participants.